Supply Response Analysis Of Indonesian Cocoa - Novi Rosilawati; Ketut Sukiyono; Sriyoto Sriyoto (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2019)
The Supply response of cocoa in Indonesia is done through an approach to the area of cocoa plantations, in response to economic factors and non-economic factors. Data analyzed from 1985 to 2015 (time series). The aim is to find out the factors that affect the area of cocoa plantations in Indonesia and the response of the offer of cocoa in Indonesia seen from the value of short-term elasticity and long-term elasticity. The partial adjustment and adaptive expectation model was applied and continued with an analysis of Seemingly Unrelated Regression Equations (SURE). The results of the analysis show that the factors affect the area of cocoa plantations in Indonesia are on smallholder plantations, namely coffee prices, rubber prices, and technology. In the state plantations, namely the previous year's cocoa plantation area, rubber prices, technology, and government policy. In private plantations, namely rubber prices, technology, and labor costs. Supply response of cocoa that is in line with the value of elasticity both short and long term is inelastic which means that it is following expectations, where the value of long-term elasticity is greater than the value of short-term elasticity